Controlled Release from Core-Shell Nanoporous Silica Particles for Corrosion Inhibition of Aluminum Alloys. (18th January 2011) - Jiang, Xingmao; Jiang, Ying-Bing; Liu, Nanguo; Xu, Huifang; Rathod, Shailendra; Shah, Pratik; Brinker, C. Jeffrey
Abstract : Cerium (Ce) corrosion inhibitors were encapsulated into hexagonally ordered nanoporous silica particles via single-step aerosol-assisted self-assembly. The core/shell structured particles are effective for corrosion inhibition of aluminum alloy AA2024-T3. Numerical simulation proved that the core-shell nanostructure delays the release process. The effective diffusion coefficient elucidated from release data for monodisperse particles in water was1.0 × 10 − 14  m 2 s for Ce 3+ compared to2.5 × 10 − 13  m 2 s for NaCl. The pore size, pore surface chemistry, and the inhibitor solubility are crucial factors for the application. Microporous hydrophobic particles encapsulating a less soluble corrosion inhibitor are desirable for long-term corrosion inhibition.